GE_GERICHTE A/2809/2005 vom 4. Oktober 2005 - GE Cour de justice (2005)
; AM ; PRIME D'ASSURANCE-MALADIE ; PRIME D'ASSURANCE ; RETARD ; COMMANDEMENT DE PAYER ; FRAIS(EN GÉNÉRAL) ; FRAIS(EN GÉNÉRAL) | LAMal.61;